Unveiling the Mycorrhizal World (IntechOpen, 2024)
Mycorrhizal fungi are widespread organisms found in various regions across the globe that are closely related to a broad range of root plant species, including agricultural crops. These fungi exhibit multiple traits that promote plant growth, and numerous studies have demonstrated their ability to increase plant growth by improving the availability and efficiency of nutrient and water uptake from the soil. Specifically, mycorrhizal fungi have been shown to increase the availability of nitrogen and phosphorus in plants. While these fungi cannot fix nitrogen from the atmosphere, they are capable of mineralizing organic matter, releasing nitrogen that is trapped in molecules and cellular organelles. In addition, arbuscular mycorrhizal fungi (AMF) can increase phosphorus availability in plants. However, high levels of phosphorus in the soil can decrease the interactions between the fungus and the host plant. Some studies have shown that mycorrhizal fungi can enhance plant tolerance to environmental stress. In summary, mycorrhizal fungi can be used to promote plant growth, improve nutrient utilization efficiency, reduce environmental impacts and production costs, and enhance plant tolerance to cope with stress conditions. The use of AMF is an excellent strategy to achieve sustainable production.